Minor Phytocannabinoids: A Misleading Name but a Promising Opportunity for Biomedical Research - Diego Caprioglio; Hawraz Ibrahim M. Amin; Orazio Taglialatela-Scafati; Eduardo Muñoz; Giovanni Appendino (Biomolecules, 2022)
Despite the very large number of phytocannabinoids isolated from Cannabis (Cannabis sativa L.), bioactivity studies have long remained focused on the so called “Big Four” [Δ9-THC (1), CBD (2), CBG (3) and CBC (4)] because of their earlier characterization and relatively easy availability via isolation and/or synthesis. Bioactivity information on the chemical space associated with the remaining part of the cannabinome, a set of ca 150 compounds traditionally referred to as “minor phytocannabinoids”, is scarce and patchy, yet promising in terms of pharmacological potential. According to their advancement stage, we sorted the bioactivity data available on these compounds, better referred to as the “dark cannabinome”, into categories: discovery (in vitro phenotypical and biochemical assays), preclinical (animal models), and clinical. Strategies to overcome the availability issues associated with minor phytocannabinoids are discussed, as well as the still unmet challenges facing their development as mainstream drugs.